Digital chronological data reuse in archaeology: Three case studies with varying purposes and perspectives. (December 2021) - Moody, Bryony; Dye, Tom; May, Keith; Wright, Holly; Buck, Caitlin
Highlights: Digital archaeological data are often not archived in a reusable format. There is insufficient data archived describing the process of building chronological models. There needs to be explicit standards for ensuring digital archaeological data are reusable. Full ADS archive search and site specific data are investigated. Abstract: A wealth of digital data are produced during an archaeological excavation and because so much of the fieldwork is unrepeatable, once the site is fully excavated, the digital records must be archived in a manner that best facilitates reuse. This paper presents three case studies of users wishing to reuse digital archaeological data from online repositories, with a specific focus on absolute and relative dating evidence. We discuss the problems encountered and how they reflect the wider issues of the reuse of digital archaeological data. Additionally, we provide recommendations specific to chronological data that seek to address the problems.